2022
DOI: 10.1111/1467-8551.12626
|View full text |Cite
|
Sign up to set email alerts
|

Socio‐emotional Wealth Preservation and Alliance Success in Family Firms: The Role of Political Instability and Alliance Management Capability

Abstract: Socio-emotional wealth preservation (SEW-P) can create a dilemma for family firms when seeking to establish strategic alliance: how to manage the need to establish strategic alliances aimed at obtaining complementary network-based resources (the economic dimension) with the fear that such a move may jeopardize family control and domination (the SEW dimension). To address this dilemma (also labelled as a 'mixed gamble'), we theorized that the concern to preserve SEW (i.e. SEW-P) can contribute to family firms' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 185 publications
0
8
0
Order By: Relevance
“…To examine the type of mediation, the results of the research indicate that it fulfils the conditions suggested by Baron and Kenny (1986), which assumes a statistically significant effect of direct relationships between variables (Al‐Tabbaa et al, 2022). First, Table 5 shows a direct effect of the paths between the dimensions of the AOM‐HR and innovation performance.…”
Section: Analysis and Findingsmentioning
confidence: 87%
“…To examine the type of mediation, the results of the research indicate that it fulfils the conditions suggested by Baron and Kenny (1986), which assumes a statistically significant effect of direct relationships between variables (Al‐Tabbaa et al, 2022). First, Table 5 shows a direct effect of the paths between the dimensions of the AOM‐HR and innovation performance.…”
Section: Analysis and Findingsmentioning
confidence: 87%
“…This uncertainty and turbulence in the Libyan environment, in turn, has encouraged the family firms to seek external knowledge, such as crisis management (OECD, 2016), to cope with constant and significant risks of social capital and political instability during and following the Arab Spring where there is a partial or complete breakdown of state authority. Similarly, these companies have become more interested in strategic alliance as an option to manage the uncertainty that increased for Libyan family and nonfamily businesses after 2011 (Abdesamed, 2014) and strengthen their position in the market (Al‐Tabbaa, Nasr, Zahoor, & de Silva, 2022; Nasr, 2019). In effect, the Libyan firms would typically have a complementary and idiosyncratic form of market knowledge, a network of operational support and contacts which play an important role in developing and sustaining success in the Libyan business sector (Mansour, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…First, most studies on AMC have been widely associated with publicly listed companies (Hohberger, Almeida, & Parada, 2015), which implies a limitation in our understanding of this capability within the family business sector. The family business is fundamentally different from other types of organizations as members of the family are heavily involved in the decision‐making process (Madanoglu, Memili, & De Massis, 2020), thus are most likely to incorporate the values and aspiration and the first generation of the family business (including the founders) would be the source of values and aspirations for later generations (Al‐Tabbaa, Nasr, Zahoor, & Silva, 2022). The values characterizing the shared objectives of a family business usually result in a higher degree of cohesiveness and commitment in the workforce, which adds to creating possible advantages over non‐family businesses, which in turn can influence their potential in building and managing alliances (Koka & Prescott, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Interactional justice ensures that both parties are valued by each other and facilitates interfirm solidarity (Luo, 2007;Wei et al, 2020), and thus the precondition of the value proposition is satisfied. Driven by the reinforced social identification between manufacturers and customers, both parties may proactively make collaborative efforts in information system usage and information content sharing to indicate long-term commitment (Al-Tabbaa et al, 2023). Firms' opportunistic behaviors will discredit their reputation and eliminate the possibility of future partnering with others, especially in China (Luo, 2007).…”
Section: Hypotheses Development 241 Relationships Between Interfirm J...mentioning
confidence: 99%